Kajian Yuridis terhadap Asas Itikad Baik dalam Pelaksanaan Putusan Pengadilan Perdata - Faiqotul, Fina; Sidi Ahyar Wiraguna (Pusat Riset dan Inovasi Nasional, 2026)
The enforcement of civil court judgments in Indonesia frequently encounters obstacles due to parties’ bad faith conduct, such as covert asset transfers or groundless resistance to execution. Although the principle of good faith is a foundational tenet in civil law, its application in the enforcement phase remains inconsistent. This study examines the concept and legal status of the good faith principle in Indonesian positive law concerning civil judgment enforcement and analyzes the legal consequences of its violation. A normative juridical method is employed, utilizing library-based research on primary and secondary legal sources. The findings reveal that while good faith is recognized in substantive civil law, it has not been explicitly incorporated into civil procedural law. Consequently, bad faith actions during enforcement rarely incur clear procedural sanctions. Theoretically, this underscores the need to integrate ethical principles into civil procedure doctrine; practically, it calls for regulatory reforms to embed good faith as a binding procedural obligation in judgment enforcement.